2016
DOI: 10.1590/1980-5373-mr-2016-0367
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous Fe2O3-Supported ZSM-5 Zeolites by Carbon-Templating and their Evaluation as Photo-Fenton Catalysts to Degrade Organic Pollutant

Abstract: Mesoporous Fe 2 O 3 -supported ZSM-5 zeolites were prepared by carbon-templating and subsequently evaluated as photo-Fenton catalysts to degrade a dye used as a model heavy organic pollutant. The synthesis procedure of the mesoporous ZSM-5 zeolites was performed employing a nucleating gel and carbon particles as mesopores template. Thereafter, the precursor salt of the iron oxide (Fe 2 O 3 ) was impregnated and then calcined to obtain the final catalyst. For comparison purposes, a conventional Fe 2 O 3 -suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
2
5
0
6
Order By: Relevance
“…It can be seen that the size and shape of particles for both samples are similar, demonstrating that the use of chitin as mesopore template did not affect the morphological characteristics of ZSM-5 crystallites. This finding is consistent with a recently reported work, where carbon particles were used as mesopore template for preparation of ZSM-5 [4]. From Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…It can be seen that the size and shape of particles for both samples are similar, demonstrating that the use of chitin as mesopore template did not affect the morphological characteristics of ZSM-5 crystallites. This finding is consistent with a recently reported work, where carbon particles were used as mesopore template for preparation of ZSM-5 [4]. From Fig.…”
Section: Resultssupporting
confidence: 93%
“…In addition, it can be observed that the intensity of XRD peaks decreases with the increasing of the chitin amount, resulting in a decrease of the relative crystallinity, whose quantitative values expressed in terms of percentage are shown in Table I. Similar results have been observed by other researchers [4], which used different amounts of carbon particles as template for the formation of mesoporous ZSM-5. Relative crystallinity was calculated according to the standard method described in the ASTM D3906-03 [19].…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations